GAYA HIDUP MAHASISWI MIGRAN DAN NON MIGRAN DI KOTA PALEMBANG (Studi Kasus: Mahasiswi Migran dan Non Migran di Universitas PGRI Palembang) - Raden Ayu Wulantari; Armansyah Armansyah (Jurnal Kependudukan Sriwijaya, 2014)
, The number of female students in Indonesia, more than men. Programs student favorite is the economic, education and health. PGRI Palembang university campus is one that has the largest number of female students compared to other private university in the city of Palembang. Migrant Students have a complex problem because in terms of their status as women, especially regarding security. Conditions that make them to be away from their parents and relatives demanding that they should be able to withstand the problems independently. This study will examine the problem of student migrants through scientific study, entitled "Migrant Student Lifestyle and Non Migrants in Palembang (Case Study: Migrants and Non-Migrants student at the University of PGRI Palembang. This study aims to look at the lifestyle of students of migrant and non-migrant in the city of Palembang. The method used is qualitative descriptive qualitative design. Source of data derived from primary and secondary sources to the type of data in the form of words, actions obtained from informants. Data collection through stages of participant observation, in-depth interviews, and documentation. Criterion validity of the data using a degree of confidence (credibility) with technical examination of the validity of data through observation extension, increase endurance, and triangulation of data. Results were analyzed using phase reduction, display, and conclusion. The results of this study demonstrate a lifestyle of migrant student is more concerned than the non-migrant student it can be seen from several indicators such as independence, activity, consumption, diet, sleep, exercise, work, security, troubleshooting.